Evaluation of Perceptions of Smile Esthetics by Dental Students - Paken Gamze; Ünal Merve (Balkan Stomatological Society, 2021)
Background/Aim: The aim of this study was to investigate in the esthetic perceptions of 2nd grade dental students before and after training.